Numerical Solution of a Multilane Traffic Flow Model - Kabir, MH; Andallah, LS (GANIT: Journal of Bangladesh Mathematical Society, 2014)
This paper performs the numerical solution of a macroscopic multilane traffic flow model based on a linear density-velocity relationship. A multilane traffic flow is modeled by a system of nonlinear partial differential equation appended with initial and boundary conditions reads as an initial boundary value problem (IBVP). We present numerical simulation of the IBVP by a finite difference scheme named Lax-Friedrichs scheme and report on the stability and efficiency of the scheme by performing numerical experiments. The computed result satisfies some well known qualitative features of the solution. GANIT J. Bangladesh Math. Soc. Vol. 33 (2013) 25-32 DOI: http://dx.doi.org/10.3329/ganit.v33i0.17653